Observation of anisotropic effect of antiferromagnetic ordering on the superconducting gap in ErNi2B2C - Bobrov, N.L.; Chernobay, V.N.; Naidyuk, Yu.G.; Tyutrina, L.V.; Yanson, I.K.; Naugle, D.G.; Rathnayaka, K.D.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The point-contact spectra of the Andreev reflection dV / dI curves of the superconducting rare-earth nickel borocarbide ErNi2B2C ( Tc ≈ 11 K) have been analyzed in the «one-gap» and «two-gap» approximations using the generalized Blonder–Tinkham–Klapwijk model and the Beloborod’ko model allowing for the pair-breaking effect of magnetic impurities. Experimental and calculated curves have been compared not only in shape, but in magnitude as well, which provide more reliable data for determining the temperature dependence of the energy gap (or superconducting order parameter) Δ(T). The anisotropic effect of antiferromagnetic ordering at TN ≈ 6 K on the superconducting gap/order parameter has been determined: as the temperature is lowered, Δ decreases by 25% in the c-direction and only by 4% in the ab-plane. It is found that the pair-breaking parameter increases in the vicinity of the magnetic transitions, the increase being more pronounced in the c-direction. The efficiency of the models was tested for providing Δ(T) data for ErNi2B2C from Andreev reflection spectra.